Tindakan Preventif Guru Pendidikan Agama Kristen dalam Menangani Kekerasan Seksual di Sekolah Kristen - Metha Putri Paraswati; Cristian Seldjatem; Nelson Hasibuan; Asor Yual; Celinedian Giroth (Jurnal Pendidikan Agama dan Teologi, 2024)
Actions to prevent sexual violence in Christian schools are an important topic in efforts to create a safe and comfortable learning environment for students. This research aims to explore various prevention strategies that can be implemented in Christian school environments, especially, to reduce incidents of violence. The research method used is qualitative methods, or library studies, where the researcher provides solutions to the problems raised by collecting various theories and information from library materials, such as books, dictionaries, journals, the Bible, and online media. Then, these sources is an academically accountable source, including literature studies and observations in schools through journal articles. The research results show that implementing violence prevention measures in schools can be effective in reducing levels of violence and creating a conducive learning climate. The practical implication of this research is the need for collaboration between schools, parents and the community in implementing holistic and sustainable preventive strategies. Further research is needed to identify factors that influence the successful implementation of violence prevention measures in schools.